2023
DOI: 10.1097/gox.0000000000004722
|View full text |Cite
|
Sign up to set email alerts
|

Closed Incision Negative Pressure Therapy versus Standard of Care in Reduction of Surgical Site Complications: A Systematic Review and Meta-analysis

Abstract: Surgical site complications (SSCs), such as surgical site infection (SSI), dehiscence, seroma, hematoma, and skin necrosis, are associated with increased patient morbidity and mortality. 1 Patients who develop SSCs often experience delayed wound healing, decreased quality of life, and increases in length of stay (LOS), medical procedures performed, pain, and potential reoperation and readmission. [1][2][3] Increased use of resources with management Reconstructive ORiginal aRticleIntroduction: Closed incision n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…However, a mix of ciNPT systems were compared to SOC dressings in the Biancari et al and Tao et al meta‐analyses, whereas the results reported in this work limited and differentiated ciNPT to two systems (ciNPT‐F and ciNPT‐MLA). While no other cardiac surgery specific meta‐analyses have been published, other published articles have assessed rates of SSI following ciNPT use 33–43 . The Singh et al meta‐analysis compared the use of ciNPT‐F and ciNPT‐MLA against SOC dressings to assess clinical outcomes after surgery, including a mix of surgical specialty types within the analysis 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a mix of ciNPT systems were compared to SOC dressings in the Biancari et al and Tao et al meta‐analyses, whereas the results reported in this work limited and differentiated ciNPT to two systems (ciNPT‐F and ciNPT‐MLA). While no other cardiac surgery specific meta‐analyses have been published, other published articles have assessed rates of SSI following ciNPT use 33–43 . The Singh et al meta‐analysis compared the use of ciNPT‐F and ciNPT‐MLA against SOC dressings to assess clinical outcomes after surgery, including a mix of surgical specialty types within the analysis 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Five meta‐analyses reported reduced SSI rates with ciNPT use compared to SOC dressings across a mix of surgical specialties and ciNPT systems 34–39 . Two ciNPT‐F‐specific meta‐analyses have reported reduced SSI with ciNPT use across all surgical specialties 40,41 . When Singh et al assessed cardiac surgery separately, ciNPT‐F also showed reduced rates of SSI when compared to SOC dressings 41 .…”
Section: Discussionmentioning
confidence: 99%
“…This contradicts several studies demonstrating decreased surgical site infection rates with ciNPWT. [5][6][7][8][9]11,13,14,30,33,36,41,[43][44][45][46][47][48][49][50][51][52][54][55][56][57][58][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] However, the occurrence of infection in DIEP flaps is infrequent, with a recent meta-analysis reporting a donor site infection rate of 4.79%. 77 Mechanistically, ciNPWT acts as a barrier that prevents contamination of the surgical site with bacteria before reepithelization, encourages drainage of excess interstitial fluid, increases lymphatic flow, improves blood flow, and induces angiogenesis, theoretically decreasing the risk of infection and expediting healing.…”
Section: Discussionmentioning
confidence: 99%
“…27,33,38 Our findings on seroma rates were similarly not statistically significant (P = 0.63). Some studies demonstrate a benefit on rates of seroma with the use of ciN-PWT, 11,41,44,49,50,52,54,55,63 but results are mixed. [6][7][8][13][14][15]33,45,48,61 Seromas develop as a result of the accumulation of serum in internal spaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation